2020
DOI: 10.1016/j.resuscitation.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Life Support 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations

Abstract: This 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With TreatmentRecommendations (CoSTR) for neonatal life support includes evidence from 7 systematic reviews, 3 scoping reviews, and 12 evidence updates.The Neonatal Life Support Task Force generally determined by consensus the type of evidence evaluation to perform; the topics for the evidence updates followed consultation with International Liaison Committee on Resuscitation member resuscitation counci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
117
0
54

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(173 citation statements)
references
References 143 publications
(176 reference statements)
2
117
0
54
Order By: Relevance
“…However, in 2010 ‘justifiable’ to stop was changed to ‘appropriate’, and in 2015 to ‘reasonable’. This contrasts with the new recommendations arguing that a reasonable timeframe to consider before ending resuscitation ‘is around’ 20 min after birth 1–5 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, in 2010 ‘justifiable’ to stop was changed to ‘appropriate’, and in 2015 to ‘reasonable’. This contrasts with the new recommendations arguing that a reasonable timeframe to consider before ending resuscitation ‘is around’ 20 min after birth 1–5 …”
Section: Discussionmentioning
confidence: 92%
“…If intravascular access is not yet available, administering endotracheal epinephrine (adrenaline) at a larger dose (0.05-0.1 mg/kg) than the dose used for intravenous administration is suggested. 5. Umbilical venous catheterisation is suggested as the primary method of vascular access during newborn infant resuscitation in the delivery room.…”
Section: For Non-vigorous Newborn Infants Delivered Through Meco-mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the male disadvantage is reported by many studies in newborn humans and animals, we have previously shown no difference between male and female newborn piglets during hypoxia, asphyxia, resuscitation, and post-resuscitation recovery (14). Current resuscitation guidelines recommend performing chest compressions (CC) at a rate of 90/min with 30 ventilations (3:1 C:V) to achieve adequate oxygen delivery (15)(16)(17). Apart from current recommendations, several interventions, namely CC with asynchronous ventilations (CCaV) and sustained inflation during chest compression (CC+SI), have also been shown to be effective during cardiopulmonary resuscitation (18,19).…”
Section: Introductionmentioning
confidence: 92%
“…Currently, epinephrine is the only medication recommended in neonatal resuscitation 1 and is indicated if the heart rate remains below 60 beats per minute (bpm) despite effective positive pressure ventilation (PPV) with 100% O 2 and chest compressions (CC). 2 3 Time to return of spontaneous circulation (ROSC) is an important prognostic indicator of outcome.…”
Section: Introductionmentioning
confidence: 99%